Comparison of brain atrophy and cognitive performance in individuals with low and high cardiovascular risk: Data from the Diabetes and Dementia (D2) Study: Neuropsychology: Neuropsychological correlates of pathology — Novel and standard cognitive markers of disease. (7th December 2020) - Restrepo, Carolina; Werden, Emilio; Singleton, Rebecca; Khlif, Mohamed Salah; Bird, Laura J.; Ekinci, Elif; MacIsaac, Richard; Srivastava, Piyush; Patel, Sheila; Burrell, Louise; Brodtmann, Amy
Abstract: Background: Growing evidence suggests that increased cardiovascular risk might accelerate brain atrophy and cognitive decline. The aim of this analysis was to investigate associations between the Framingham Risk Score (FRS), brain volume and cognitive function in individuals with type 2 diabetes (T2DM) participating in the Diabetes‐and‐Dementia (D2) study. Method: Ninety cognitively‐normal participants with T2DM completed neuropsychological assessments, health‐and‐lifestyle questionnaires, 24‐hour ambulatory blood pressure monitoring and a 3T‐MRI scan. FreeSurfer (version 6.0) was used to estimate total brain volume (TBV), mean cortical thickness and subcortical volumes, including the thalami and caudate nuclei. TBV was expressed as a percentage of intracranial volume. Averages between left and right volumes were calculated for subcortical structures. The sample was divided into low (n=45) and high (n=45) FRS groups based on the median score ( X =39.7). Differences in volumes were compared between groups. Four cognitive domains, including visuospatial skills, verbal memory, language, and executive functions & speed of processing information, were derived using a factor analysis. These domains were used to compare cognitive performance between individuals with low and high FRS. Result: Participants in the high FRS group were significantly older and had a lower percentage of women: age (F (1, 89)=26.6; p <0.000); sex (x 2 =10.07, p =0.01). The high FRS group, after correcting for age and sex, had significantly smaller TBV (F (1, 86)=60.6; p =0.023) and reduced cortical thickness (F (1, 82)=9.93; p =0.002). No difference was found in other subcortical structures. Multivariate analysis revealed a statistically significant difference in cognition between individuals with low and high FRS (F (1, 85)=4.46, p=0.003). Univariate analyses showed statistically significant differences in executive function & processing speed (F (1, 81) = 5.69; p =0.019), with the low FRS group outperforming the high FRS group. Conclusion: High cardiovascular risk in T2DM is associated with accelerated structural brain aging, manifesting as cerebral atrophy and poorer cognitive function, particularly in processing speed and executive function.